THE INFLUENCE OF NEW WAYS OF WORKING (NWOW) ON WORK ENGAGEMENT WITH PROACTIVE PERSONALITY AND JOB CRAFTING AS MEDIATORS - Cheryl Dhewina, Wong; Victoria, Jonathan (2021)
Employees’ work engagement is one of the important outcomes to identify whether the employees are enjoying their work. Currently, New Ways of Working (NWOW) are increasingly being adopted in the workplace to suit the needs of a diverse workforce, with the aim of increasing work engagement. NWOW research is currently scarce, particularly in terms of the effects on people's work engagement and organisational performance. This paper contributes to an initial framework to examine the relationships of NWOW and work engagement, with proactive personality and job crafting as mediators. Identifying this relationship has the potential to contribute to work engagement and NWOW literature, and to human resource development practice.